PENGUKURAN DAN ANALISIS GRAVITY UNTUK PENENTUAN PROSPEK MINERALISASI BIJIH BESI DI DAERAH SUNGAI PADANG, SIJUK, BELITUNG - Eddy Supriyana; Budy Santoso; Bambang Wijatmoko (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Research with Gravity method has been done in Padang River Village of Belitung Province. The purpose of this research is to know the pattern of the potential spread of iron ore, to localize the spread of iron ore and to determine the position of rock intrusion containing mineralization. Gravity data obtained from the measurement results, then modeled to estimate the price of rock density from some subsurface layer. Based on the value of the  density contrast  is correlated with the porosity (small), then the rock characteristics will be identified so that the tendency of the existence of Seal rocks and Trapping sources can be known. Gravity measurements are done systematically with intervals between observation stations on one line of 25 meters, while the distance between lines of about 500 meters. Bouguer anomaly in the study area ranged from -5 until 75 mGal, forming as low and high anomaly. The height of the Anomaly Bouguer occupies the western part of the study site, its value reaches 30 mGal and to the north of the research area reaches 42 mGal, the height of the North-South trending anomaly flanked by two high anomaly groups.Keywords: Gravity, Bouguer Anomaly, Density, Iron Ore, Mineralization